2015
DOI: 10.1002/wrna.1288
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant messenger RNA technology and its application in cancer immunotherapy, transcript replacement therapies, pluripotent stem cell induction, and beyond

Abstract: In recent years, the interest in using messenger RNA (mRNA) as a therapeutic means to tackle different diseases has enormously increased. This holds true not only for numerous preclinical studies, but mRNA has also entered the clinic to fight cancer. The advantages of using mRNA compared to DNA were recognized very early on, e.g., the lack of risk for genomic integration, or the expression of the encoded protein in the cytoplasm without the need to cross the nuclear membrane. However, it was generally assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 302 publications
(284 reference statements)
0
63
0
Order By: Relevance
“…Furthermore, Holtkamp et al ., have shown that 2 copies of 3′ UTR from β-globin result in increased protein levels and mRNA stability only in immature dendritic cells, whereas in mature dendritic cells, no effect could be observed18. Cell specificity of UTRs when combined with mRNA has been also observed for other cells and tissues and has been discussed in the recent reviews4142.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, Holtkamp et al ., have shown that 2 copies of 3′ UTR from β-globin result in increased protein levels and mRNA stability only in immature dendritic cells, whereas in mature dendritic cells, no effect could be observed18. Cell specificity of UTRs when combined with mRNA has been also observed for other cells and tissues and has been discussed in the recent reviews4142.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the identification of novel diagnosis and treatment methods is required. The roles of mRNAs in eukaryotic cells have been well characterized; they are important in regulating gene expression and may be promising in cancer therapies (22,23). Notably, eukaryotic cellular mRNAs possess distinctive sections at their 5'-and 3'-ends.…”
Section: Discussionmentioning
confidence: 99%
“…Cell type and cell state have a strong impact on how the cell reacts to variations in artificially introduced mRNA sequences. 42,[50][51][52] The biological implications of these modifications need to be carefully evaluated. UTRs are key elements in the mRNA sequence for translation initiation, elongation, and termination as well as intracellular localization and mRNA stability, 53,54 all of which have a significant impact on final protein expression kinetics.…”
Section: Discussionmentioning
confidence: 99%